2005
DOI: 10.1007/s10157-004-0333-8
|View full text |Cite
|
Sign up to set email alerts
|

Correction of CAPD catheter displacement using alpha-replacement method

Abstract: The alpha-replacement method for a displaced CAPD catheter proved to be effective and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
(2 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, the benefit of fluoroscopic manipulation is that it is minimally invasive. In this study as well, the success rate of alpha-replacement treatment was similar to the rate in previous reports [9,10], which was lower than that of surgical procedures. In contrast, we were able to perform alpha-replacement treatment without complications such as abdominal organ injury or hernia that accompany surgical procedures.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…On the other hand, the benefit of fluoroscopic manipulation is that it is minimally invasive. In this study as well, the success rate of alpha-replacement treatment was similar to the rate in previous reports [9,10], which was lower than that of surgical procedures. In contrast, we were able to perform alpha-replacement treatment without complications such as abdominal organ injury or hernia that accompany surgical procedures.…”
Section: Discussionsupporting
confidence: 67%
“…This wire is unique in being flexible if straightened, becoming harder when coiled [10]. We used the alpha-replacer in the same manner as previously described [9]. After checking the position of the tip of the PD catheter using a radio-contrast agent, an alpha-replacer is inserted aseptically (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first limitation is the high rate of recurrence, which was 22% (2 of 9 cases) in functional terms and 33% (3 of 9 cases) in radiological terms in the present series. High recurrence rates for TRC were also reported by Kawamoto et al , reaching 43% (6 of 14 cases) (3). Conversely, Santarelli et al reported a 1-year survival rate lower than 30% for video laparoscopically rescued catheters (4).…”
Section: Discussionmentioning
confidence: 53%
“…Our medical center frequently admits patients with these complications from community medical units. Application of motion, enemas, massage, guide wire and other traditional methods is effective for some of the patients [20][21][22][23][24][25] . However, in the vast majority of patients, especially those with omental wrap, surgical repositioning 3.…”
Section: Discussionmentioning
confidence: 99%